Решение:
![4^{x} - 3*2^{x} - 4 < 0 4^{x} - 3*2^{x} - 4 < 0](https://tex.z-dn.net/?f=+4%5E%7Bx%7D++-+3%2A2%5E%7Bx%7D++-+4+%3C+0+)
![(2^{x})^{2} - 3*2^{x} - 4 < 0 (2^{x})^{2} - 3*2^{x} - 4 < 0](https://tex.z-dn.net/?f=+%282%5E%7Bx%7D%29%5E%7B2%7D++-+3%2A2%5E%7Bx%7D++-+4+%3C+0++)
Пусть
0 " alt=" 2^{x} = t, t > 0 " align="absmiddle" class="latex-formula">, тогда
![t^{2} - 3*t - 4 < 0 t^{2} - 3*t - 4 < 0](https://tex.z-dn.net/?f=+t%5E%7B2%7D++-+3%2At++-+4+%3C+0+)
![(t - 4)*(t + 1) < 0 (t - 4)*(t + 1) < 0](https://tex.z-dn.net/?f=+%28t+-+4%29%2A%28t+%2B+1%29+%3C+0+)
0, t + 1 > 0, " alt=" t > 0, t + 1 > 0, " align="absmiddle" class="latex-formula"> тогда
![0 < t < 4 0 < t < 4](https://tex.z-dn.net/?f=+0+%3C+t+%3C+4+)
Получили, что
![0 < 2^{x} < 4 0 < 2^{x} < 4](https://tex.z-dn.net/?f=+0+%3C+2%5E%7Bx%7D+%3C+4++)
![2^{x} < 2^{2} 2^{x} < 2^{2}](https://tex.z-dn.net/?f=+2%5E%7Bx%7D+%3C+2%5E%7B2%7D+)
Так как 2 > 1, то x < 2,
x∈ (- ∞ ; 2).
Ответ: (- ∞ ; 2).